2016
DOI: 10.1103/physrevb.94.165402
|View full text |Cite
|
Sign up to set email alerts
|

Quantum confinement effects on optical transitions in nanodiamonds containing nitrogen vacancies

Abstract: Colored nitrogen-vacancy (NV) centers in nanosize diamonds (d∼5 nm) are promising probe materials, because their optical transitions are sensitive to mechanical, vibrational and spin changes in the surroundings. Here, a linear response time-dependent density functional theory approach is used to describe the optical transitions in several NV-doped diamond quantum dots (QDs) in order to investigate size effects on the absorption spectra. By computing the full optical spectrum up to band-to-band transitions, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 66 publications
2
44
0
Order By: Relevance
“…14 Doping introduces new subband-gap levels, and it has been shown that NV centers in diamond give rise to new dopant-centered sp 3 − sp 3 mid-gap electronic transitions and charge-transfer (CT or "photoionization") excited states. 22 Similar applications in quantum information processing 23 have been shown for the negatively-charged silicon-vacancy (SiV − ) center due to its short fluorescent lifetime, narrow emission line-width, and high percentage of photons (∼70-80%) emitted through its zero-phonon line (ZPL). 24,25 This defect has also been shown to be useful as a high-resolution high-pressure sensor.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…14 Doping introduces new subband-gap levels, and it has been shown that NV centers in diamond give rise to new dopant-centered sp 3 − sp 3 mid-gap electronic transitions and charge-transfer (CT or "photoionization") excited states. 22 Similar applications in quantum information processing 23 have been shown for the negatively-charged silicon-vacancy (SiV − ) center due to its short fluorescent lifetime, narrow emission line-width, and high percentage of photons (∼70-80%) emitted through its zero-phonon line (ZPL). 24,25 This defect has also been shown to be useful as a high-resolution high-pressure sensor.…”
Section: Introductionmentioning
confidence: 84%
“…They were constructed using the bulk face-centered cubic lattice parameter 7 a 0 = 0.357 nm and hydrogen atoms were used to passivate the surface dangling bonds, according to the procedure presented in Ref. 22. The sizes of these quantum dots are similar to the smallest nano-diamonds obtainable by detonation or laser-heated diamond anvil cell synthesis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal of this work is to analyze the efficiency of the recently developed functionals in the framework of double‐hybrid density functional theory (DH‐DFT), as the widely adopted models from the highest rung of DFT approximations, for predicting oxidation energies of organic compounds from different categories prone to be employed as shuttle molecules candidates. Although several works in the framework of DFT using conventional functionals, with emphasis on oxidation energies as well as other energetic and spectroscopic properties, have been carried out in recent years, it is necessary to evaluate the accuracy of the DH functionals for computational description of oxidation energies of shuttle molecules. In turn, this leads to unveiling the range of the accountability of modern DFT approximations and identifying improvement areas for design of novel DHs.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods deal with the polaron dynamics and include Ehrenfest dynamics [16,17], time-dependent density functional theory (TDDFT) [18], the multiconfiguration time-dependent Hartree method [19], its multilayer formulation [20] and the hierachical equations of motion [21,22]. TDDFT has been proven particularly successful in studying phenomena involved in polaron formation and dynamics, such as transient vibration energy redistribution and spectroscopy [23] and defects in nanomaterials [24,25].…”
mentioning
confidence: 99%